Literacia em saúde dos cuidadores de crianças pré-escolares e a sua relação nas práticas alimentares saudáveis. - Moita, Marina Pereira (2024)
The dietary profile of children has been altered by the increased intake of ultra-processed products of low nutritional quality, which can have repercussions on nutritional deficiencies. Involving the family in promoting healthy eating practices is therefore essential. It is also important to consider this family's Health Literacy levels to ensure a comprehensive understanding and its repercussions on daily healthy eating practices. OBJECTIVE: To analyze the Health Literacy of caregivers and its relationship with the healthy eating practices of pre- school children. METHODOLOGY: Cross-sectional study with a quantitative approach carried out in Sobral, Ceará, Brazil. Five day-care centers were chosen and the caregivers of pre-school children were selected. The following instruments were used: characterization of the Social Determinants of Health (characteristics of the space, the family, the mother and the child); analysis of knowledge about the child's diet and health literacy; food consumption and eating habits; and assessment of the nutritional status of the children using the Z score for age and the mothers. They were analyzed descriptively and inferentially using the Chi-Square test and for those with observed values less than five, Fisher's Exact test was performed using the Jamovi software. The level of statistical significance was set at 5% (p<0.05) with a 95% confidence interval. The study was approved by the Research Ethics Committee of the State University of Paraíba. RESULTS: There was a significant relationship between Health Literacy and the presence of the mother (p<0.007), the schooling of the head of the family (p<0.005), the schooling of the mother (p<0.004), resilience (p<0.005), Health Literacy related to the promotion of a healthy lifestyle (p<0.001), milk consumption (p<0.024) during the week and bean consumption (p<0.007) during the weekend. There was also a significant relationship between health literacy in promoting a healthy lifestyle and the intake of vegetables (p<0.047) and sweets (p<0.036), and the number of meals eaten during the day (p<0.015). With regard to nutritional status, the mother's height being less than 1.55 cm was statistically related to an adequate level of Health Literacy (p<0.001). CONCLUSION: The level of Health Literacy was adequate and was related to the level of education of the caregivers. It was inferred that the better the level of Health Literacy, the easier it is to understand guidelines for promoting a healthy lifestyle. Although caregivers understand and offer healthy foods to children, unhealthy foods are still frequently eaten.